Combining photoinduced linkage isomerism and nonlinear optical properties in ruthenium nitrosyl complexes. Issue 6 (21st November 2019) - Mikhailov, Artem; Vuković, Vedran; Kijatkin, Christian; Wenger, Emmanuel; Imlau, Mirco; Woike, Theo; Kostin, Gennadiy; Schaniel, Dominik
Abstract : Double optical functionality of a ruthenium nitrosyl compound is achieved by the combination of photoswitching of the nitrosyl ligands, giving rise to photochromic behaviour, with the second‐harmonic generation enabled by the alignment of the molecular dipoles in the non‐centrosymmetric structure of trans ‐[RuNO(NH3 )4 F]SiF6 . Abstract : The complex trans ‐[RuNO(NH3 )4 F]SiF6 was synthesized in quantitative yield and the structure was characterized by X‐ray diffraction and spectroscopic methods. The complex crystallizes in the non‐centrosymmetric space group Pn . Hirshfeld surface analysis revealed that the dominant intermolecular interactions are of types H…F and F…O, which are likely to be responsible for the packing of the molecules in a non‐centrosymmetric structure. Irradiation with blue light leads to the formation of Ru–ON (metastable state MS1) and Ru–η 2 ‐(NO) (metastable state MS2) bond isomers, as shown by IR and UV–Vis spectroscopy. The structural features of the MS1 isomer were elucidated by photocrystallography. The complex exhibits exceptionally good thermal stability of the metastable state MS1, such that it can be populated by light at 290–300 K, which is important for potential applications. The second harmonic (SH) emission can be generated by femtosecond‐pulsed irradiation of the complex. The generated SH is rather efficient and stable under long‐term exposure. Finally, since both metastable states and harmonic generation can be generated at room temperature, an attempt to drive the SH response by photoisomerization of the nitrosyl ligand was made and is discussed.